Fire resistance of RC columns using finite element method - Guo, Gillian Yihui. (2009)
This report investigates the fire resistance of reinforced concrete (RC) columns at elevated temperatures using the finite element programme SAFIR. The thermal and structural analyses for the calculation of fire resistance of columns are explained.